Assessment of competencies and capabilities of spatial design thinking among students in higher education universities in Malaysia - Mohd Lasa, Ahmad Lutfee; Abdul Rahman, Ahmad Rizal; Daud, Nuraini (Human Resource Management Academic Research Society, 2024)
Design thinking in design education has been observed to enhance understanding of design direction and has gained nationwide recognition. Its usage among industrial design students in design schools could improve teaching methods and strengthen students' design capabilities. Spatial ability within design thinking gave the Industrial design student the knowledge to expand comprehension towards design projects at early stages. This study uses survey research to examine 102 industrial design students' spatial design thinking skills, such as visualising, imagining, and reasoning, in Malaysian higher education institutions. This study found that incremental spatial ability improves students' comprehension of design activities. This study demonstrates the efficacy of design thinking in enhancing students' ability to identify and resolve design challenges.